Community Assembly Processes of the Microbial Rare Biosphere. Issue 9 (September 2018) - Jia, Xiu; Dini-Andreote, Francisco; Falcão Salles, Joana
Abstract : Our planet teems with microorganisms that often present a skewed abundance distribution in a local community, with relatively few dominant species coexisting alongside a high number of rare species. Recent studies have demonstrated that these rare taxa serve as limitless reservoirs of genetic diversity, and perform disproportionate types of functions despite their low abundances. However, relatively little is known about the mechanisms controlling rarity and the processes promoting the development of the rare biosphere. Here, we propose the use of multivariate cut-offs to estimate rare species and phylogenetic null models applied to predefined rare taxa to disentangle the relative influences of ecoevolutionary processes mediating the assembly of the rare biosphere. Importantly, the identification of the factors controlling rare species assemblages is critical for understanding the types of rarity, how the rare biosphere is established, and how rare microorganisms fluctuate over spatiotemporal scales, thus enabling prospective predictions of ecosystem responses. Highlights: Increasing sequencing depth efforts and the number of replicates, and performing standardized benchmarking analyses, will improve the resolution of rare biosphere dynamics across spatiotemporal scales. The rare biosphere dominates microbial communities, and often accounts for important ecosystem services. Technical procedures limit our understanding of the rare biosphere. The detection of rare taxa should be based on multivariate cut-offs, by removing rare OTUs until removal influences community similarity. Different types of rarity are structured by interplay in community assembly processes. Determining assembly processes for rare species is essential to understand if they differ from processes governing abundant microbes. Understanding the ecological processes structuring each type of rarity is essential to know how the rare biosphere might respond to environmental changes.